Clinicopathological and prognostic value of epithelial cell adhesion molecule in solid tumours: a meta-analysis - Ding, Peiwen; Chen, Panyu; Ouyang, Jiqi; Li, Qiang; Li, Shijie (Frontiers in Oncology, 2023)
Background Malignant tumors, mainly solid tumors, are a significant obstacle to the improvement of life expectancy at present. Epithelial cell adhesion molecule (EpCAM), a cancer stem cell biomarker, showed widespread expression in most normal epithelial cells and most cancers. Although the clinical significance of EpCAM in various malignant solid tumors has been studied extensively, the latent relationships between EpCAM and pathological and clinical characteristics in solid tumors and differences in the roles of EpCAM among tumors have not been clearly determined. The destination point of this study was to analyze the value of EpCAM in solid tumors in clinicopathological and prognostic dimension using a meta-analysis approach. Method and materials A comprehensive and systematic search of the researches published up to March 7th, 2022, in PubMed, EMBASE, Web of Science, Cochrane library and PMC databases was performed. The relationships between EpCAM overexpression, clinicopathological characteristics, and survival outcomes were analyzed. Pooled hazard ratios (HRs) with 95% confidence intervals (CIs) and odds ratios (ORs) were estimated as indicators of the degree of correlation. This research was registered on PROSPERO (International prospective register of systematic reviews), ID: CRD42022315070. Results In total, 57 articles and 14184 cases were included in this study. High EpCAM expression had a significant coherence with a poorer overall survival (OS) (HR: 1.30, 95% CI: 1.08–1.58, P < 0.01) and a worse disease-free survival (DFS) (HR: 1.58, 95% CI: 1.28–1.95, P < 0.01), especially of gastrointestinal tumors’ OS (HR: 1.50, 95% CI: 1.15–1.95, P < 0.01), and DFS (HR: 1.84, 95% CI: 1.52–2.33, P < 0.01). The DFS of head and neck tumors (HR: 2.33, 95% CI: 1.51–3.61, P < 0.01) was also associated with the overexpression of EpCAM. There were no positive relationships between the overexpression of EpCAM and sex (RR: 1.03, 95% CI: 0.99–1.07, P = 0.141), T classification (RR: 0.93, 95% CI: 0.82–1.06, P = 0.293), lymph node metastasis (RR: 0.85, 95% CI: 0.54–1.32, P = 0.461), distant metastasis (RR: 0.97, 95% CI: 0.84–1.10, P = 0.606), vascular infiltration (RR: 1.05, 95% CI: 0.85–1.29, P = 0.611), and TNM stage (RR: 0.93, 95% CI: 0.83–1.04, P = 0.187). However, the overexpression of EpCAM exhibited a significant association with the histological grades (RR: 0.88, 95% CI: 0.80–0.97, P < 0.01). Conclusion Based on pooled HRs, the positive expression of EpCAM was totally correlated to a worse OS and DFS in solid tumors. The expression of EpCAM was related to a worse OS in gastrointestinal tumors and a worse DFS in gastrointestinal tumors and head and neck tumors. Moreover, EpCAM expression was correlated with the histological grade. The results presented pointed out that EpCAM could serve as a prognostic biomarker for gastrointestinal and head and neck tumors. Systematic review registration https://www.crd.york.ac.uk/prospero, identifier CRD42022315070.